2001
DOI: 10.1046/j.1365-3016.2001.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for spontaneous preterm birth in two urban areas of Ukraine

Abstract: The economic, social and health problems faced by former eastern bloc countries after the demise of the Soviet Union are unique in the recent history of Europe. We conducted a study in two urban areas of Ukraine, asking if the traditional predictors of preterm delivery continue to be associated with risk under these conditions. Subjects were pregnant women with last menstrual period (LMP) between 25 December 1992 and 23 July 1994. Self-completed questionnaires and the medical record provided data. We compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
1
5
0
8
Order By: Relevance
“…Net maternal weight‐gain was observed to have a positive effect on minimizing PTB in the univariate analysis of the present study but the variable was not eligible for inclusion in the final multivariate model. In two other studies 38,44 however, net pregnancy weight‐gain was demonstrated to be a risk factor even in the multivariate analysis. As weight‐gain depends on the duration of gestation, the association between weight‐gain and PTB could be an overestimation.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Net maternal weight‐gain was observed to have a positive effect on minimizing PTB in the univariate analysis of the present study but the variable was not eligible for inclusion in the final multivariate model. In two other studies 38,44 however, net pregnancy weight‐gain was demonstrated to be a risk factor even in the multivariate analysis. As weight‐gain depends on the duration of gestation, the association between weight‐gain and PTB could be an overestimation.…”
Section: Discussionsupporting
confidence: 71%
“…It seems to have varied according to the cut‐off selected. With regard to younger age, ages less than both 18 and 20 years have been reported as significant 36–38 and the cut‐off for older age selected has been 30, 37,39 35 40 and 40 years or older, 41 all of which have been reported as being significant. Age was not found to be a risk factor in two studies 36,42 where the cut‐off was 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…Preterm delivery is often classified into spontaneous and medically indicated subgroups, and the majorities (75–85%) of PTDs are spontaneous [5]. The causes and underlying biological mechanisms of spontaneous PTD are still unclear [6], although previous studies have identified a long list of risk factors, including low socio-economic status [7], parity, maternal age [8], drug abuse, life events [9], racial origin [10], maternal active or passive smoking [11], air pollution [12], [13] intrauterine infection [14], and genetic heterogeneity [9], [15].…”
Section: Introductionmentioning
confidence: 99%
“…A study from Lithuania identified low income, low education, and unemployment during pregnancy as independent risk factors for low birthweight after adjustment for other socio‐economic factors 31 . However, the previously mentioned study in Ukraine found only a weak relationship between maternal education and marital status and preterm birth 32 . Although the situation in the post‐communist countries of central and eastern Europe is quite different from the former Soviet Union, a study from the Czech Republic found the gap in mean birthweight between mothers with primary education and those with university education to be even wider, at 182 g in 1989 and grew further to 256 g in 1996 33 …”
Section: Discussionmentioning
confidence: 88%